2019
DOI: 10.1021/acs.jafc.9b03159
|View full text |Cite
|
Sign up to set email alerts
|

Production of Rare Ginsenosides Rg3 and Rh2 by Endophytic Bacteria from Panax ginseng

Abstract: The ginsenosides Rh2 and Rg3 induce tumor cell apoptosis, inhibit tumor cell proliferation, and restrain tumor invasion and metastasis. Despite Rh2 and Rg3 having versatile pharmacological activities, contents of them in natural ginseng are extremely low. To produce ginsenosides Rh2 and Rg3, the saponin-producing capacity of endophytic bacteria isolated from Panax ginseng was investigated. In this work, 81 endophytic bacteria isolates were taken from ginseng roots by tissue separation methods. Among them, stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 38 publications
0
26
0
Order By: Relevance
“…According to one study [22], ginsenoside Rh2 has the advantages of low toxicity, low molecular weight, and good fat solubility. And its ability to inhibit the proliferation and migration of tumor cells and angiogenesis has been well documented [23]. One study [24] reported that ginsenoside Rh2 affected tumorigenesis through regulating encoded proteins or encoded RNAs [24].…”
Section: Discussionmentioning
confidence: 99%
“…According to one study [22], ginsenoside Rh2 has the advantages of low toxicity, low molecular weight, and good fat solubility. And its ability to inhibit the proliferation and migration of tumor cells and angiogenesis has been well documented [23]. One study [24] reported that ginsenoside Rh2 affected tumorigenesis through regulating encoded proteins or encoded RNAs [24].…”
Section: Discussionmentioning
confidence: 99%
“…that could hydrolyse glucosidic linkages at C-20 and C-3 of ginsenosides converting Rb1 to Rg3 [ 29 ]. A bacterial endophyte from roots of P. ginseng with ginsenoside conversion abilities is Agrobacterium rhizogenes that converted common ginsenosides into the rare ginsenosides F2, Rg3 and Rh2 [ 30 ]. In P. notoginseng , the bacterial endophytes Brevundimonas and Bacillus could convert Rg1 to Rh1 and Rg1 to vinaginsenoside possibly via glycosyltransferase and oxidase activities, respectively [ 31 ].…”
Section: Ginseng Interactions With Bacterial Endophytesmentioning
confidence: 99%
“…Evidence thus far for archaeal endophytes in ginseng comes from a metagenomics study of DNA extracted from healthy disinfected root tissue, where 5% of the reads matched archaeal sequences, but no further description was provided [ 30 ]. While much lower than the 81% of reads matching bacteria, it was not that much lower than the 12% of reads matching eukaryotes, presumably mostly fungi.…”
Section: Ginseng Archaeal Endophytesmentioning
confidence: 99%
“…Endophytic fungi are also considered as a promising and novel resource of natural bioactive compounds, which could be applied in the medicine, food, agriculture and cosmetics industries (Zhao et al 2011;Hyde et al 2019). Among them, some products are the same as those produced by their host plants, such as taxol (Stierle et al 1993), camptothecine (Shweta et al 2013), vinblastine (Yin and Sun 2011), ginsenosides Rg3 and Rh2 (Yan et al 2019), tanshinone I and IIA (Ming et al 2012), indicating that endophytic fungi have the ability to produce their host plant-derived bioactive compounds.…”
Section: Introductionmentioning
confidence: 99%